The Effect of Natural Resource Profit-Sharing Funds and Investment on Regional Gross Domestic Product Through Regional Expenditure in Kutai Timur Regency - Selly Swandari; Swadia Gandhi; Akbar Lufi Zulfikar (El-Qish: Journal of Islamic Economics, 2024)
This study examines the influence of natural resource revenue sharing funds (DBH SDA) and investment on Gross Regional Domestic Product (GRDP) through regional spending in the East Kutai Regency. This study aims to assess how these variables affect regional economic development, focusing on the role of government spending in mediating the influence. Using path analysis with multiple linear regression modeling, this study analyzes time series data. The results show that DBH SDA has a significant positive effect on regional spending, which means that increasing revenue from natural resources will encourage an increase in regional spending. In contrast, investment does not show a significant effect on regional spending, indicating the fluctuating nature and delayed impact of investment on regional development. Furthermore, both DBH SDA and investment have a direct effect on GRDP, with investment having a positive effect, while DBH SDA has a negative effect. Regional spending has a positive effect on GRDP, indicating the importance of government spending efficiency in driving economic growth. This study suggests that although DBH SDA directly affects regional spending, its effect on GRDP is more mediated by government spending, while investment has a more direct impact on regional economic growth. These findings provide valuable insights for policymakers in East Kutai Regency to optimize resource allocation and investment strategies to achieve sustainable economic development.